2015
DOI: 10.1002/stem.2027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signature of erythroblast enucleation in human embryonic stem cells

Abstract: While enucleation is a critical step in the terminal differentiation of human red blood cells, the molecular mechanisms underlying this unique process remain unclear. To investigate erythroblast enucleation, we studied the erythroid differentiation of human embryonic stem cells (hESCs), which provide a unique model for deeper understanding of the development and differentiation of multiple cell types. First, using a two-step protocol, we demonstrated that terminal erythroid differentiation from hESCs is direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 46 publications
1
32
0
5
Order By: Relevance
“…The recent report of Rouzbeh et al [41] demonstrated that it might be possible to increase the percentage of cells undergoing enucleation by reducing the expression of micro RNA30a (MIR30a); however, there was very little, if any, cell expansion in their system. Furthermore, knockdown of an MIR is a difficult strategy to use routinely, whereas identification of the MIR30a targets and development of small molecules effectors would increase the utility of the method and could be easily tested in the high-yield, highly defined differentiation system reported here.…”
Section: Discussionmentioning
confidence: 99%
“…The recent report of Rouzbeh et al [41] demonstrated that it might be possible to increase the percentage of cells undergoing enucleation by reducing the expression of micro RNA30a (MIR30a); however, there was very little, if any, cell expansion in their system. Furthermore, knockdown of an MIR is a difficult strategy to use routinely, whereas identification of the MIR30a targets and development of small molecules effectors would increase the utility of the method and could be easily tested in the high-yield, highly defined differentiation system reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Scalable, clinically compatible protocols to produce erythroid cells from hPSCs have been developed but progress to translation has been hampered by the lack of terminal maturation of the resultant cell. In contrast to RBCs generated in vitro from adult bone marrow or mobilised peripheral blood CD34 1 progenitors cells, erythroid cells produced from both hESCs and iPSCs have a fragile morphology, a poor enucleation rates and express embryonic and foetal rather than adult globin [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…MDSC expansion, function and migration are controlled by miR-494 [19], miR-155 [17,20,21], miR-21 [17], miR-210 [22] and miR-9 [16]. Recent studies have reported that miR-30 can regulate the differentiation and function of many cell types, such as mesenchymal stem cells [23,24] and human embryonic stem cells [25]. Our previous study also found that miR-30a attenuated the immunosuppressive functions of IL-1b-elicited mesenchymal stem cells [26].…”
Section: Introductionmentioning
confidence: 99%